Bacterial and fungal pattern recognition receptors in homologous innate signaling pathways of insects and mammals - Stokes, Bethany A.; Yadav, Shruti; Shokal, Upasana; Smith, L. C.; Eleftherianos, Ioannis (Frontiers in Microbiology, 2015)
In response to bacterial and fungal infections in insects and mammals, distinct families of innate immune pattern recognition receptors initiate highly complex intracellular signaling cascades. Those cascades induce a variety of immune functions that restrain the spread of microbes in the host. Insect and mammalian innate immune receptors include molecules that recognize conserved microbial molecular patterns. Innate immune recognition leads to the recruitment of adaptor molecules forming multi-protein complexes that include kinases, transcription factors and other regulatory molecules. Innate immune signaling cascades induce the expression of genes encoding antimicrobial peptides and other key factors that mount and regulate the immune response against microbial challenge. In this review, we summarize our current understanding of the bacterial and fungal pattern recognition receptors for homologous innate signaling pathways of insects and mammals in an effort to provide a framework for future studies.